2012
DOI: 10.5539/jms.v2n2p247
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamics of Monetary and Fiscal Policy as a Tool for Economic Growth: Evidence from Nigeria

Abstract: The study investigated the dynamics of Nigeria's monetary and fiscal policies, focusing specifically on the effects on the growth of Nigerian economy. The fundamental objective is to examine the effect of monetary and fiscal policy in Nigerian economic growth. The paper employed the Engle-Granger and Johansen-Joselius method of co-integration in a VECM setting. The empirical results demonstrated that there exist a long-run linear relationship between the dependent variable and the explanatory variables, meanin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 1 publication
1
9
0
Order By: Relevance
“…Similarly, the estimated result shows that government revenue and economic growth have a significant positive relationship in Nigeria in the short run but the relationship becomes negative in the long run, though not significant. This finding is in line with the submission of Falade and Folorunsho [8], Ogege and Shiro [9] in related studies but different methodologies in Nigeria. However, recurrent expenditure has a significant negative relationship with economic growth in the short run but the result becomes insignificant in the long run.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Similarly, the estimated result shows that government revenue and economic growth have a significant positive relationship in Nigeria in the short run but the relationship becomes negative in the long run, though not significant. This finding is in line with the submission of Falade and Folorunsho [8], Ogege and Shiro [9] in related studies but different methodologies in Nigeria. However, recurrent expenditure has a significant negative relationship with economic growth in the short run but the result becomes insignificant in the long run.…”
Section: Resultssupporting
confidence: 91%
“…This conclusion is supported by the propositions of Nworji, Okwu, Obiwuru, and Nworji [21] Medee and Nenbee [23], Wu, Tang, and Lin [23] and Philip [24]. But contradicts the submission of Omitogun and Ayinla [9]…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…The paper concluded that fiscal and monetary policies had galvanized government to commit budgetary management which would also address anomalies in the financial system. Ogege and Shiro (2012) however, investigated the dynamics of Nigeria's monetary and fiscal policies, focusing specifically on their effects on the growth of Nigerian economy. The study revealed that both monetary and fiscal policy contributed to the growth of Nigerian economy.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…While some scholars advocated for a sharp departure from monetary policy targeting to inflation targeting, others recommended the hybrid of both as being practiced in Kenya (Kamaan, 2014). Yet, others have called for a complete reformation of policies where fiscal and other potent measures be used as compliments to monetary policy (Akujuobi, 2010; Onoh, 2002; Fasanya and Onakoya, 2013; Ogege and Shiro, 2012).…”
Section: A Review Of Related Literaturementioning
confidence: 99%